Understanding cognitive flexibility in emotional evaluation in autistic males and females: the social context matters - Adeline Lacroix; Yoann Bennetot-Deveria; Monica Baciu; Frédéric Dutheil; Valentin Magnon; Marie Gomot; Martial Mermillod (Molecular Autism)
Abstract Background Autistic individuals often have difficulty flexibly adjusting their behavior. However, laboratory experiments have yielded inconsistent results, potentially due to various influencing factors, which need to be examined in detail. This study aimed to investigate the hypothesis that the social content of stimuli could play a specific role in some of the flexibility challenges faced by autistic individuals. The second aim was to explore sex differences in this context. Methods We analyzed data from 256 adult participants (124 with autism), matched on age, gender, and sex, who performed an emotional shifting task involving unpredictable shifts between positive and negative stimuli. Additionally, the task included both social and non-social conditions. Results Our results revealed a larger switch cost in the social than in the non-social condition, and this was more pronounced in autistic than in non-autistic individuals. Furthermore, we observed that autistic females differed from autistic males in the non-social condition and from non-autistic females in the social condition. Limitations The online nature of the study reduced the control over participant conditions. In addition, further studies are needed to investigate whether these results apply to the broader autism spectrum. Conclusions Building on previous research demonstrating a greater switch cost in autistic than non-autistic individuals for socio-emotional stimuli, our study further extends these findings by highlighting that the social context, rather than the emotional nature of the stimuli alone, may play a significant role in the flexibility challenges faced by autistic individuals. Our findings also contribute to the literature on sex differences in autism.